Differential agonist sensitivity of glycine receptor α2 subunit splice variants - Miller, Paul S (2004)
1. The glycine receptor (GlyR) α2A and α2B splice variants differ by a dual, adjacent amino acid substitution from α2A(V58,T59) to α2B(I58,A59) in the N-terminal extracellular domain. 2. Comparing the effects of the GlyR agonists, glycine, β-alanine and taurine, on the GlyR α2 isoforms, revealed a significant increase in potency for all three agonists at the α2B variant. 3. The sensitivities of the splice variants to the competitive antagonist, strychnine, and to the biphasic modulator Zn(2+), were comparable. In contrast, the allosteric inhibitor picrotoxin was more potent on GlyR α2A compared to GlyR α2B receptors. 4. Coexpression of α2A or α2B subunits with the GlyR β subunit revealed that the higher agonist potencies observed with the α2B homomer were retained for the α2Bβ heteromer. 5. The identical sensitivity to strychnine combined with a reduction in the maximum current induced by the partial agonist taurine at the GlyR α2A homomer, suggested that the changed sensitivity to agonists is in accordance with a modulation of agonist efficacy rather than agonist affinity. 6. An effect on agonist efficacy was also supported by using a structural model of the GlyR, localising the region of splice variation to the proposed docking region between GlyR loop 2 and the TM2-3 loop, an area associated with channel activation. 7. The existence of a spasmodic mouse phenotype linked to a GlyR α1(A52S) mutation, the equivalent position to the source of the α2 splice variation, raises the possibility that the GlyR α2 splice variants may be responsible for distinct roles in neuronal function.